"You're in the Army Now:" The Impact of World War II on Women's Education, Work, and Family. (24th February 2014) - Jaworski, Taylor
Abstract : World War II temporarily halted the rise in high school and college graduation rates. This article shows that manpower mobilization for World War II decreased educational attainment among high school-age females during the early 1940s, reduced employment and earnings, and altered decisions regarding family formation. I then provide evidence that women in this cohort returned to school in later life and relate these findings to the "quiet revolution" taking place as women learned about the benefits of school and work over the second half of the twentieth century. "Education has been ever in the nation's service. But in these days of total war that service has a new significance. 'You're in the Army now' is no cliché–it is an expression of national necessity." 1